The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10620-006-9288-9
|View full text |Cite
|
Sign up to set email alerts
|

Breath Hydrogen Test in the Diagnosis of Environmental Enteropathy in Children Living in an Urban Slum

Abstract: The aim of this study was to evaluate the breath hydrogen test in the diagnosis of small intestine bacterial overgrowth associated with asymptomatic environmental enteropathy in children living in an urban slum. Fifty school-age children living in a slum and 50 children who attended a private health clinic in the same town were included in the study. Breath hydrogen test was carried out after the administration of lactulose or glucose on two different days. Bacterial overgrowth was diagnosed when the hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 15 publications
1
56
0
1
Order By: Relevance
“…9,11 The gut microbiome of infants in developing countries differs significantly from that of infants in industrialised countries, with higher rates of bacterial overgrowth, increased parasitic load and "tropical enteropathy.' 9,[32][33][34] The interaction of gut microbes with rotavirus vaccine may reduce the titer of vaccine virus available to infect the target cells within the small intestine, where viral replication occurs to induce immune responses. Thus it is possible that the composition of the intestinal microbiota influences vaccine immune responses, and contributes to the decreased vaccine efficacy observed in Africa and Asia.…”
Section: Hypotheses For Reduced Efficacy Of Rotavirus Vaccines In Devmentioning
confidence: 99%
“…9,11 The gut microbiome of infants in developing countries differs significantly from that of infants in industrialised countries, with higher rates of bacterial overgrowth, increased parasitic load and "tropical enteropathy.' 9,[32][33][34] The interaction of gut microbes with rotavirus vaccine may reduce the titer of vaccine virus available to infect the target cells within the small intestine, where viral replication occurs to induce immune responses. Thus it is possible that the composition of the intestinal microbiota influences vaccine immune responses, and contributes to the decreased vaccine efficacy observed in Africa and Asia.…”
Section: Hypotheses For Reduced Efficacy Of Rotavirus Vaccines In Devmentioning
confidence: 99%
“…No control group was used nor comparison of breath tests to other populations made[5]. Dos Reis and colleagues expanded on these findings in a study where fifty asymptomatic children aged 5 to 11 years old living in an urban slum in Brazil were compared to a matched control group of fifty children who lived in the same city but had the financial resources to seek healthcare at a private clinic[4]. Prevalence of SIBO in the slum dwelling children was 37.5%, whereas only 2.1% of the control group had the condition.…”
Section: Sibo Associated With Unsanitary Living Conditionsmentioning
confidence: 99%
“…Poor sanitation in low-income countries could lead to higher exposure to fecal bacteria and increased incidence of enteric infection. The continuous exposure to fecal bacteria could result in bacterial overgrowth in the small intestine; numerous studies have found such overgrowth in children living with EE symptoms, by utilizing hydrogen breath tests (Fagundes Neto et al, 1994; Khin-Maung-U et al, 1992; dos Reis et al, 2007) or direct sampling of the small intestinal aspirate (Heyworth and Brown, 1975; Omoike and Abiodun, 1989). This overgrowth of microbes may cause the pathological changes characteristic of EE, in particular, villous blunting, increased intestinal permeability, and chronic inflammation that impair the proximal small intestine and subsequently reduce nutrient absorption (Lin et al, 2013; Ngure et al, 2014; Weisz et al, 2012).…”
Section: Ibd As a Platform To Understand Other Intestinal Diseasesmentioning
confidence: 99%